RISE AND FALL IN SARS-COV-2 GLOBAL PANDEMIC STRAIN RATE–AN OVERVIEW - ANWA, ABDULLAH; CHANDEL, VISHAL SINGH; SINGH, SATYENDRA PRATAP; SINGH, SATYA PRAKASH; ANWAR, NEDA (International Journal of Applied Pharmaceutics, 2021)
After its discovery in Hubei in China in December 2019, the deadly rise of modern coronavirus (COVID-19 or 2019-nCoV) has spread globally. SARS-CoV-2 disease COVID-19 has quickly spread worldwide, posing a serious threat to health and the economy. As of 25th January 2021, more than 100 million confirmed cases of 2,165,581 deaths have been reported by WHO and Worldometer. Many of the cases reported are caused by infection from human to human and are the carriers of this lethal coronavirus. Due to its calamitous nature, the whole world was under lockdown restricting all sorts of movements and means of transportation in hampering the countries economic balance. Presently, the world's endeavor to create and develop a safe and effective COVID-19 vaccine is bearing the fruit. A handful of vaccines now have been authorized around the globe and many more remain in the development phase. In addition, social isolation and knowledge of hygiene (facial masks and sanitizers) are potential methods of controlling the further dissemination of global pandemics COVID-19. This research article presents a brief overview of the catastrophic effect caused by COVID-19 disease globally and particularly in different states of India. Additionally, the article also discusses the recent variant of SARS-CoV-2 and its vulnerable impact. Furthermore, the article investigates the currently available vaccines and those in their development phase for the treatment of COVID-19 disease. This investigatory literature may provide comprehensive details on COVID-19 disease from its inception to grow and later fall in its strain rate.